Tradition, Misconception, and Contribution: Chinese Influences in Philippine Culture - Miclat, Maningning C. (Humanities Diliman: A Philippine Journal of Humanities; Vol 1 No 2 (2000), 2007)
This paper discusses Chinese influence on Philippine arts and crafts, as shown in artifacts from the Sino-Philippine trade of pre-Hispanic times-the churches, religious icons, and paintings of the Spanish period-and in the contemporary art of the Chinese Filipinos. The Chinese traditional elements are given new meanings in a new environment, and it is these misconceptions and misinterpretations of the imported concepts that influence and enrich our culture.